2020
DOI: 10.1038/s41598-020-78659-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disturbances by forest elephants on diversity of trees and insects in tropical rainforests on Mount Cameroon

Abstract: Natural disturbances are essential for tropical forests biodiversity. In the Afrotropics, megaherbivores have played a key role before their recent decline. Contrastingly to savanna elephants, forest elephants’ impact on ecosystems remains poorly studied. Few decades ago, forests on Mount Cameroon were divided by lava flows, not being crossed by a local population of forest elephants until now. We assessed communities of trees, butterflies and two guilds of moths in the disturbed and undisturbed forests split … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
(69 reference statements)
1
12
0
Order By: Relevance
“…Habitat structure has also been shown to influence elevational and non-elevational patterns of species richness and abundance of Lepidoptera in previous studies in the Afrotropics [ 17 , 30 , 56 ]. Along an elevational gradient on Mount Kilimanjaro Axmacher & Fiedler (2008) [ 57 ] reported that geometrid moth diversity (Fisher’s α) was higher in open than closed habitats, which is consistent with our findings from the Uluguru Mountains.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Habitat structure has also been shown to influence elevational and non-elevational patterns of species richness and abundance of Lepidoptera in previous studies in the Afrotropics [ 17 , 30 , 56 ]. Along an elevational gradient on Mount Kilimanjaro Axmacher & Fiedler (2008) [ 57 ] reported that geometrid moth diversity (Fisher’s α) was higher in open than closed habitats, which is consistent with our findings from the Uluguru Mountains.…”
Section: Discussionmentioning
confidence: 89%
“…Along an elevational gradient on Mount Kilimanjaro Axmacher & Fiedler (2008) [ 57 ] reported that geometrid moth diversity (Fisher’s α) was higher in open than closed habitats, which is consistent with our findings from the Uluguru Mountains. Maicher et al [ 17 ] also have recently reported a significant interaction between elevation and elephant-caused habitat disturbance on Mount Cameroon with higher butterfly species richness in more disturbed or open sites on Mount Cameroon at lower (1100 m) elevations than at higher (1850 m) elevations. We hypothesize that higher butterfly species richness and abundance in open than in closed habitats along an elevational gradient in the Uluguru Mountains may be a result of higher light intensity and thus abundance of food resources and/or host plants for larval and adult stages.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…via trampling damage; Terborgh et al 2015, Rosin et al 2017). Forest elephants induce a reduction in stem density, resulting in reduced competition amongst trees and the development of larger trees with higher wood density, positively impacting carbon sequestration (Berzaghi et al 2019, Maicher et al 2020). They also preserve the forest richness and diversity by dispersing the seeds of many species (Campos‐Arceiz & Blake 2011).…”
Section: Introductionmentioning
confidence: 99%